Índices de um cinema de poesia em Eraserhead - Santos, Leo Diniz (2007)
The present work consists in study how con figure the relation between Language and Cinema, identifing the Cinema in his linguistic and semiologic nature. The Cinema like a tongue or language, and how the Cinema structure his narrative in the classic model and the vanguard. In this direction, we bo rds conceptualy the Cinema in two theories: one, like an element from real production, codificated like a Language accord Christian Metz or; Pasolini sugests a semiology that trancends the cinematographic theory and proposes a comprehension of own reality – comprehension that the Cinema is an excellence model. The objectiv of this investigation is realise an analisys accords a model of saussurean struturalist language that was presented by Metz, and from the David Lynch films, in special the film Eraserhead (1967). Some characteristcs of narrative styles of this director, approach to the Poetry Cinema, while Contemporary Language, elaborated by Pasolini. In this analysis emphasis a similarity between Poetry Cinema and a delirius conception, from Michel Fouc ault. This research intends to contribute with a probability to normalise a model of delirant language and contemporary presented in the Linch films, specialy in the film ‘Eraserhead’